Preclinical Investigation of Pharmaceuticals Impact Against Cytochrome P450 Activity and Prognosis of Substrate Affinity as Means for Providing Substrate Therapy Safety - E. V. Fomin; I. H. Baychorov; E. V. Shih; Zh. M. Sizova (Антибиотики и Химиотерапия)
Tricyclic antidepressants, not influencing the P450 3A4 activity, are safe in combination with drugs of other groups used in the treatment of comorbid patients. Azaphen is is one of the agents most widely used in the clinical practice. The in vitro electrochemical analysis showed that pipofezin (azaphen) was not a substrate, inductor, and/or inhibitor of cytochrome P450 CYP3A4 isoenzymes. The Guzar programme computer modelling and the literature data demonstrated the substrate affinity of pipifezin to CYP1A2.